Literature Review on Herbs that Treat Type 2 Diabetes Mellitus (T2DM) - Tan, Yi Huey (2015)
Type 2 Diabetes Mellitus (formerly noninsulin-dependent diabetes mellitus (NIDDM) or adult-onset diabetes) is a metabolic disorder that is characterized by hyperglycemia (high blood sugar) in the context of insulin resistance, meaning the body doesn’t react properly to insulin or their pancreas doesn’t produce enough insulin to maintain a normal glucose level. This study is carried out to identify the herbs that can treat Type 2 Diabetes Mellitus. Numerous journals have been studied to discover herbs that are able to reduce blood glucose. The herbs that possess hypoglycemic effect are determined and the data are compiles and recorded. The herbs studied are proven through pharmacological experiments to have hypoglycemic effect. However, the mechanism of treating diabetes for some of the herbs is still unclear, thus related research remains to be further studied.